2022
DOI: 10.1016/j.dib.2021.107674
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-small cobalt particles embedded in titania by ion beam synthesis: Additional datasets including electron microscopy, neutron reflectometry, modelling outputs and particle size analysis

Abstract: This Data-in-brief article includes datasets of electron microscopy, polarised neutron reflectometry and magnetometry for ultra-small cobalt particles formed in titania thin films via ion beam synthesis. Raw data for polarised neutron reflectometry, magnetometry and the particle size distribution are included and made available on a public repository. Additional elemental maps from scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS) are also presented. Data were obtained using the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In this study, the four morphologies had no significant effect on the adhesion of BMSCs, probably because of the insufficient significant differences in the roughness and lateral spacing between fibres, and cell migration was guided by material morphology, Yi et al [38] found that huvECs migrated more favourably along parallel aligned fibres than in the vertical direction. In contrast, Qu et al [39] investigated the effect of silk fibroin fibres with different arrangements on the migration of MSCs compared with random fibres of the same diameter. MSCs exhibited higher migration efficiency on the aligned fibres.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the four morphologies had no significant effect on the adhesion of BMSCs, probably because of the insufficient significant differences in the roughness and lateral spacing between fibres, and cell migration was guided by material morphology, Yi et al [38] found that huvECs migrated more favourably along parallel aligned fibres than in the vertical direction. In contrast, Qu et al [39] investigated the effect of silk fibroin fibres with different arrangements on the migration of MSCs compared with random fibres of the same diameter. MSCs exhibited higher migration efficiency on the aligned fibres.…”
Section: Discussionmentioning
confidence: 99%